2005
DOI: 10.1111/j.1600-6143.2005.01015.x
|View full text |Cite|
|
Sign up to set email alerts
|

Homocysteine‐Lowering Therapy and Early Progression of Transplant Vasculopathy: A Prospective, Randomized, IVUS‐Based Study

Abstract: Although observational studies suggest that hyperhomocysteinemia may be a risk factor for coronary allograft vasculopathy (CAV), prospective data on homocysteine-lowering interventions and CAV development are lacking. We, therefore, randomized 44 de novo heart transplant (HT) recipients to 15 mg/day of 5-methyl-tetrahydrofolate (n = 22), or standard therapy (control group, n = 22) to investigate the effect of homocysteine lowering on the change in coronary intimal hyperplasia during the first 12 months after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…It is now well established that administration of folic acid results in significant lowering of plasma total homocyst(e)ine (2,47,64,67), but the results of several large folate therapy clinical trials to reduce the progression of cardiovascular disease have been disappointing (1,12,31,34,43,64), while showing promise in others (48,53,58). These findings argue against the hypothesis that homocysteine itself is the causative agent of disease, per se.…”
Section: Introductioncontrasting
confidence: 51%
“…It is now well established that administration of folic acid results in significant lowering of plasma total homocyst(e)ine (2,47,64,67), but the results of several large folate therapy clinical trials to reduce the progression of cardiovascular disease have been disappointing (1,12,31,34,43,64), while showing promise in others (48,53,58). These findings argue against the hypothesis that homocysteine itself is the causative agent of disease, per se.…”
Section: Introductioncontrasting
confidence: 51%
“…Potena et al have reported a significant decrease in coronary intimal hyperplasia with folate supplementation in de novo heart transplant patients with hyperhomocysteinemia. Interestingly intimal hyperplasia increased in patients receiving folate without baseline hyperhomocysteinemia (53). The metabolic and/or physiological mechanisms involved with the development of homocystinemia and the benefits of reducing this state, will require additional investigations in cardiac transplant recipients.…”
mentioning
confidence: 97%
“…A more recent randomized trial of the folate therapy on de novo heart transplant recipients during the first 12 months after transplant, as detected by IVUS, does not seem to affect on early CAV onset. 41 Numerous studies suggest that homocysteine is a modifiable risk factor for atherosclerotic diseases. In general, epidemiologic studies show an independent and graded association between homocysteine levels and cardiovascular risk.…”
Section: Hyperhomocysteinemiamentioning
confidence: 99%